Teacher Feedback and Cooperative Learning in the University Context: A Systematic Review - Lozano Moreno, Cesar; Cangalaya Sevillano, Luis Miguel (Revista Ecos de la Academia, 2026)
In the university context, teacher feedback and cooperative learning stand out as fundamental pedagogical strategies with the potential to optimize the teaching and learning process. The purpose of this research is to conduct a systematic review of the available literature to delve into the analysis of the impact that these practices have on academic performance and the experiences of students in university settings, both in specifying the processes of teacher feedback and analyzing the process of cooperative learning, based on the objective of each of the consulted studies, the methodological type of each study, considering sample and instrument, as well as the main result and highlighted conclusion. A systematic literature review was conducted based on PRISMA guidelines, analyzing 22 scientific articles published between 2016 and 2024, using the Scopus database. The results show that in these publications there is a predominance of qualitative and mixed approaches. Based on the relationship between the two initial categories, it is observed that their results and conclusions are mostly positive, highlighting aspects such as academic performance, communication skills, attitude toward learning, adaptability, and active student participation.